BACTERIAL PROFILES AND THEIR ANTIBIOTIC SUSCEPTIBILITY PATTERNS IN NEONATAL SEPSIS AT TERTIARY CARE HOSPITAL TAMILNADU:A RETROSPECTIVE STUDY - Dr.Swamy Naidu Dasari; Dr.J.Ashok Raja; Dr.K.Senthil Kumar; Dr.D.S.Jothi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background:Neonatal septicemia remains a leading cause of mortality and morbidity in developing countries such as India, representing a significant and ongoing global public health challenge.This study aimed to investigate the bacteriological profile and antibiotic resistance patterns of microorganisms isolated in cases of neonatal sepsis. Methodology: This retrospective study was conducted in the NICU of a tertiary care hospital in Tamil Nadu, from August 2024 to October 2024. Neonates presenting with clinical signs of sepsis and confirmed by positive blood cultures were included.Blood cultures were collected using aseptic techniques, and antibiotic susceptibility was tested. Empiric treatment was started with ciprofloxacin and gentamycin, upgraded if necessary. Data were analyzed using SPSS, with Fisher’s exact test for categorical variables. Results: Among 170 neonates (54% males, 46% females), 63.5% were born at <37 weeks of gestation, and 44.1% weighed 1.5–2.5 kg. The primary reasons for admission were respiratory support (26.5%), IUGR (18.8%), prematurity (14.7%), PROM (13.5%), and meconium-stained liquor (10.6%). The most common gram-negative organisms were NFGNB (22.9%), Klebsiella species (21.8%), and E. coli (12.4%). Gram-positive pathogens included Staphylococcus aureus (18.2%) and Coagulase-negative Staphylococcus (17.6%).Antibiotic Sensitivity:Gram-positive bacteria (S. aureus, Coagulase-negative Staphylococcus): high sensitivity to vancomycin, linezolid, and cefoxitin.Gram-negative bacteria: Klebsiella (doxycycline 97.3%, piperacillin-tazobactam 86.5%, imipenem 56.8%), Non-Fermentative Gram-Negative Bacilli (NFGNB) exhibited good sensitivity to Doxycycline (92.3%) and Piperacillin-Tazobactam (76.9%), with moderate sensitivity to Gentamycin (66.7%) and Ceftazidime (56.4%). E. coli (imipenem 90.5%).Antibiotic Resistance:Gram-positive: Coagulase-negative Staphylococcus (penicillin 76.7%, erythromycin 80%), S. aureus (penicillin 19.4%).Gram-negative: Klebsiella (amoxicillin 64.9%), E. coli (amoxicillin 76.2%, ciprofloxacin 50%), NFGNB (ceftazidime 38.5%). These findings emphasize the need for tailored antimicrobial use based on resistance patterns. Conclusion:. The study highlights a high prevalence of neonatal infections caused by Non Fermentative Gram Negative Bacilli(NFGNB) Klebsiella species, Staphylococcus aureus, Coagulase-negative Staphylococcus, and E. coli. Gram-positive organisms showed high sensitivity to vancomycin and linezolid, while gram-negative organisms like NFGNB exhibited good sensitivity to Doxycycline and Piperacillin-Tazobactam , with moderate sensitivity to Gentamycin and Ceftazidime ., Klebsiella and E. coli were most sensitive to piperacillin-tazobactam and imipenem,gentamycin,doxycyclin. Significant resistance was noted to penicillin and erythromycin in gram-positive bacteria, and to amoxicillin and ciprofloxacin in gram-negative bacteria. These findings emphasize the need for targeted antimicrobial therapy based on local resistance patterns and regular surveillance to optimize neonatal sepsis management.